Evaluasi Penggunaan Analgetik Dan Efektivitasnya Pada Pasien Kanker Organ Reproduksi Wanita Di Rsud Dr. Moewardi Tahun 2015 - Ayatulaila, Isne, Hidayah Karuniawati, M. Sc ., Apt (2016)
Cancer is a condition of cell which has lost its control and normal cell mechanism, so that the cell undergoes abnormal, fast, and uncontrollable growth. One of cancer patient's complaints is pain. Pain occurs because the tumor mass is getting bigger and beggir and metastasis. The number of patient cancer in Indonesia in 2013 is around 347,792 people and those who underwent pain were as many as 25%. This research aims to know the precision of analgesic therapy and its effectiveness in the patients of female reproduction organ cancers in RSUD (Regional Hospital) Dr. Moewardi in 2015. The significance of this research is to evaluate the precision and the effectiveness of analgesic in the patients of female reproduction organ cancers, therefore, it is hoped to be able to reach a therapeutic effect. This research is included in non-experimental research through a method of purposive sampling. The data collection is retrospectively from the medical record data of the patients of female reproduction organ cancers (Breast Cancer, Ovarium Cancer, Cervix Cancer, Vulva Cancer, and Endometrium Cancer) in RSUD Dr. Moewardi in 2015 and being analyzed descriptively and analytically using Wilcoxon test and Mann Whitney U test. The population of sample is as many as 35 patients who got analgesic therapy. The results of the analysis of treatment profil can be concluded that the analgesic therapy starting from the biggest number is Ketorolac 36,54%; Paracetamol 23,08%; Dexketoprofen Trometamol (KetesseR) 11,55%; Mefenamic Acid 9,62% and each 1,92% for Tramadol, Codeine, Morphine, Fentanyl, Ibuprofen, AnalsikR (methampyron dan Diazepam), and methampyron (AntrainR). The results of evaluation on the medicine precision is 100% that is precise to the indication; 91,43% is precise to the patient; 81,25% is precise to the medicine; and 88,46% is precise to the dosage. The results of the calculation of SPSS of Mann Whitney U test is p value 0.329; it was concluded that there was no difference in effectiveness between single analgesic therapy and analgesic therapy combination. The result of the Wilcoxon test is that the single analgesic group is not effective in reducing the pain scale P=(0.677) and the result of conclusion that the combined analgesic group is effective in reducing the pain scale of the patients P=(0,039).